2021
DOI: 10.1186/s13098-021-00762-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum total bilirubin, obesity and type 2 diabetes

Abstract: Background This study aims to examine the cross-sectional association between serum total bilirubin (STB) and type 2 diabetes (T2D) risk in the general population, and whether obesity could moderate this association. Methods We used data from the 1999–2018 National Health and Nutrition Examination Surveys (NHANES), including a total of 38,641 US adult participants who were 18 years or older. The STB was classified as the low, moderate, and high gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The top locus included an eQTL for UGT1A3 , which is directly involved in bilirubin metabolism. Although the cluster suggests a positive association between bilirubin levels and T2D risk, previous studies have demonstrated a negative association 22 . In addition, bile acid sequestrants may be used for treatment of T2D 23 ; however, the link between bile acid sequestrants and serum bilirubin levels is uncertain.…”
Section: Discussionmentioning
confidence: 68%
“…The top locus included an eQTL for UGT1A3 , which is directly involved in bilirubin metabolism. Although the cluster suggests a positive association between bilirubin levels and T2D risk, previous studies have demonstrated a negative association 22 . In addition, bile acid sequestrants may be used for treatment of T2D 23 ; however, the link between bile acid sequestrants and serum bilirubin levels is uncertain.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, many investigations have shown that bilirubin is a regulator with multiple biological functions [ 17 , 18 ]. Slightly elevated bilirubin has been connected to a reduced incidence of cardiovascular events, diabetes, and metabolic syndrome [ 19 21 ]. In contrast to these studies, the subjects included in the current study were healthy patients, and the direct interaction between bilirubin levels and CVDs, diabetes, and metabolic syndrome cannot be derived from the present research, but some differences were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this association with abnormal glucose tolerance tests was reported as early as 1996 [ 10 ]. Numerous clinical studies reporting lower serum/plasma bilirubin concentrations with the risk of diabetes (and its complications) were published in the following decade, as summarized in 2012 [ 11 ], as well as being confirmed in more recent studies [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 92%